Adherence with Therapeutic Regimen among Chronic Renal Failure Patients Undergoing Maintenance Hemodialysis - Hanan Zaid Essa Alessa; Ibrahim Abdullah Abumuti; Sabah Abdullatif Alotaibi; Amwaj Thaar F Alotaibi; Layla Abdullatif Alghebiwi; Abdulaziz Mohammed Albattal; Abdullah Mohammed Albattal; Albandari Zowayed Barakai Almutairi; Khaled Farhan Al Ruwaili; Samia Monier Alotaibi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Adherence with the prescribed medical regimen is a crucial factor for achieving good therapeutic results in dialysis patients. This study aimed to: Assess adherence of chronic renal failure patients undergoing maintenance hemodialysis with therapeutic regimen. Subjects and Method: Setting: In the dialysis Unitat university hospitals, Saudi Arabia. Subjects: A convenience sample of200 adult patients with CRF admitted to Hemodialysis Units at Scheduled. Three tools were used, Tool (I) Structured interview schedule. Tool (II)Patient’s knowledge assessment questionnaire, Tool (III) GR-Simplified Medication Adherence Questionnaire Hemodialysis. Results : It was observed that vast majority (83%) of studied patients had adherence with medication , more than two third (68.5%) of studied patients had adherence with follow up , while more than half (55.5%) had in-adherence with dietary instructions and (44.5%) had adherence .there was a high positive significant correlation between knowledge score and adherence . Conclusion: the results revealed that studied patients with good knowledge score appeared adherence with the GR-SMAQ-HD scale, while studied patients who had poor knowledge appeared In-adherence. Recommendations: Counseling should be provided for all patients who are undergoing Hemodialysis that helps in preparation of them and give advice in adherence of therapeutic regimen.